The Role of Artificial Intelligence In Urban Tourism Cultural Communication - Irwanti, Marlinda; Angelita, Gloria; Ceasaria, Rauda; Hasyim, Yunus (Magister of Communication Science, Sahid University Jakarta., 2024)
Technological progress is developing massively amidst the frenzied issues of trade wars, ideological wars and intellectual wars. Conditions like this require humans to continue to work with spectacular innovations to survive and face change. Technology is the result of modern human culture which needs to be supported by human abilities and potential in fulfilling their life needs, both materially and spiritually. Every human being has different levels of needs in primary and secondary aspects, all adapted to their respective lifestyles and cultural backgrounds. The primary aspects in the mission of human life are food, shelter and clothing. Secondary aspects balance and support primary needs, namely creativity, work and initiative to increase happiness in life. Technology is a creative force and work that is continuously updated and equipped for every human need in their life interactions, namely: work, family and the surrounding environment. Intention drives the spiritual aspects that humans need, even though they are invisible, such as: the desire to be happy, to relieve fatigue. Jakarta, as a busy urban city, densely populated, densely built, with high pollution, makes its people depressed and difficult to be happy. Traveling is a human effort to create happiness and provide new experiences. The existence of technology as a good communication tool makes it easier for people to get various tourist information that is right for them. In the current digital era, tourist arenas are created in modern programs even with AI technology. Artificial Intelligence is present in the tourism sector with innovative work that can be enjoyed by many people from various countries with different cultures and languages. This research aims to reveal the role of AI in urban tourism cultural communication, descriptive research types and data collection methods by conducting in-depth interviews and literature studies.